Differences on Subordination Indexes in Expositive and Argumentative Texts Written in Japanese and Spanish [Diferencias en Los Índices de Subordinación en Textos Expositivos y Argumentativos Escritos en Japonés y Español] - Muñoz-Arias, E (Pontificia Universidad Catolica de Chile, 2014)
The purpose of this study is to demonstrate the existence of significant differences regarding the way in which speech is organized in Japanese and in Spanish, specifically regarding the frequency and use of subordinate clauses, so as to verify the textual stylistic differences between both languages. In order to do that, the syntactic complexity of each was measured by applying some of Kellog Hunt s Syntactic Indexes (1970). Texts in Japanese and Spanish, written by "linguistically competent adults"-Academics, writers, columnists, etc.-(Véliz, 1999) were compared and displayed within two text types: Expositive and argumentative (Hatim & Mason, 1995 [1990]). The results show that, in fact, there are significant differences, since the texts written in Japanese in the said types stated above show a higher frequency of subordinate clauses.